Isolation, propagation and rapid molecular detection of the Kalahari truffle, a mycorrhizal fungus occurring in South Africa - Adeleke, Rasheed Adegbola (Rhodes University, Faculty of Science, Department of Biochemistry, Microbiology and Biotechnology, 2007)
Terfezia pfeilii is an edible mycorrhizal fungus that thrives in the Kalahari Desert of southern Africa. It is best known by desert dwellers for its flavour and as a source of nutrition. Although the genus Terfezia is generally regarded as being an ectomycorrhizal mycobiont, the exact mycorrhizal type formed by T. pfeilli and its' associated host plants remains uncertain. Discovery of the host plants for T. pfeilii would first be required in order to further investigate the life cycle and cultivation of this truffle. This study focussed on the isolation of mycelia from the ascocarp, optimising the growth conditions of the mycelial cultures, rapid molecular identification of T. pfeilii, investigation of potential helper bacteria and mycorrhizal synthesis experiments. T. pfeilii ascocarps were harvested from the Spitskop Nature Reserve in Upington, South Africa. Ascocarps were successfully identified using both morphological and molecular methods. Despite the delayed growth mostly caused by contaminating microorganisms, the isolation of T. pfeilii mycelia culture was successful. Molecular techniques were used to confirm the identity of the pure culture. Further studies were conducted on ways to improve the growth conditions of the mycelial culture on Fontana medium. An optimum temperature of 32Â°C, the addition of Bovine Serum Albumin as a nitrogen source and a pH of 7.5 significantly improved the growth of T. pfeilii in vitro. A rapid PeR-based molecular method was developed to speed up the identification of T. pfeilii. Specific primers that can exclusively amplify the ITS region of T. pfeilii were designed and used to identify both the ascocarps and the mycelial culture. The specificity of these primers was confirmed by their inability to amplify DNA from the isolates of contamining fungi obtained during the isolation process. Molecular comparison was made to confirm the reclassification of South African samples of T. pfeilii as Kalaharituber pfeilii as proposed by Ferdman et al.,(2005). However, in this study, the name T. pfeilii has been retained. A total of 17 bacterial isolates were obtained from the fruiting bodies of T. pfeaii and these were tested for stimulation of mycelial growth in vitro, indole production and phosphate solubilising capabilities. Bacterial isolates that showed potential to be Mycorrhization Helper Bacteria (MHB) were identified as Paenibacillus sp., Bacillus sp. and Rhizobium tropici. Selected plant seedlings were inoculated with T. pfeilii cultures or ascocarp slurry in order to re-establish the mycorrhizal association. After 8 months, light microscopy observations revealed an endomycorrhizal type association between Cynodon dactylon and T. pfeilii. This was confirmed with molecular analysis using specific T. pfeilii ITS primers. After 15 months, molecular methods confirmed Acacia erioloba as another host plant. These results have provided essential information paving the way for further investigation into the life cycle and biology of the Kalahari truffle.,KMBT_363,Adobe Acrobat 9.53 Paper Capture Plug-in
Keywords: Truffles -- Kalahari Desert; Fungi -- Identification; Mycorrhizal fungi -- South Africa; Edible fungi -- South Africa; Mushroom culture -- South Africa; Fungi -- Cultures and culture media -- South Africa; Truffles -- South Africa; Truffles -- Lifecycles; Mycorrhizal fungi -- Lifecycles